Komunikasi Terapeutik Purnomo dengan ODGJ Dalam Konten Youtube "Purnomo Belajar Baik" - Tamano, Indah Puspita; Rahmawati, Dian Hutami (Jurnal Pustaka Komunikasi, 2026)
This study aims to analyze Purnomo's therapeutic communication practices in interactions with people with mental disorders (ODGJ) in the YouTube account "Purnomo Belajar Baik" (Purnomo Belajar Baik). This study used a qualitative approach with content analysis of five videos depicting interactions between Purnomo and people with mental disorders. The analysis was conducted based on the stages of therapeutic communication, communication characteristics, and communication techniques used in each interaction. The results show that Purnomo's interactions reflect communication characteristics such as sincerity, empathy, and warmth, as well as the use of communication techniques such as active listening, questioning, clarification, and providing emotional support. Therapeutic communication practices in this study are understood as a form of recovery-oriented communication, namely communication that aims to build a sense of security, increase self-confidence, and support the psychological recovery process of people with mental disorders. This distinguishes therapeutic communication from ordinary interpersonal communication, as therapeutic communication has the specific goal of helping individuals achieve a more stable and adaptive emotional state. The research findings indicate that the principles of therapeutic communication can be applied in non-clinical contexts through a humanistic approach that emphasizes acceptance, emotional support, and positive interpersonal relationships between the communicator and the person with mental disorders.